Prediction of the Endocrine disruption profile of fluorinated biphenyls and analogues: An in silico study. (February 2023) - Zhong, Yuyan; Ren, Jing; Li, Rui; Xuan, Yuxin; Yao, Wu; Yang, Qianye; Gan, Yin; Yu, Shuling; Yuan, Jintao
Abstract: Fluorinated biphenyls and their analogues (FBAs) are considered new persistent organic pollutants, but their endocrine-disrupting effects are still unknown. To fill this gap, the binding probability of 44 FBAs to different nuclear hormone receptors (NHRs) was predicted using Endocrine Disruptome. And molecular similarity and network toxicology analysis were used to strengthen the docking screening. The docking results showed that FBAs could have high binding potential for various NHRs, such as estrogen receptors β antagonism (ERβ an), liver X receptors α (LXRα), estrogen receptors α (ERα), and liver X receptors β (LXRβ). The similarity analysis found that the degree of overlap of the NHR repertoire was related to the Tanimoto coefficient of FBAs. Network toxicology verified a part of docking screening results and identified endocrine-disrupting pathways worthy of attention. This study found out potential endocrine-disrupting FBAs and their vulnerable, and developed a workflow that would leverage in silico approaches including molecular docking, similarity, and network toxicology for risk prioritization of potential endocrine-disrupting compounds. Graphical abstract: Image 1 Highlights: Endocrine-disrupting potential of 44 FBAs was predicted in silico . FBAs with high similarity had similar NHR targets. AR, ERβ, and MR are vulnerable target receptors of FBAs. The degree of overlap of NHR was related to the Tanimoto coefficient of FBAs. 96 targets of FBAs expression were analyzed by network toxicology.